Real-life experience of ceritinib in crizotinib-pretreated ALK+ advanced non-small cell lung cancer patients. Issue 1 (13th February 2018) - Cadranel, Jacques; Cortot, Alexis B.; Lena, Hervé; Mennecier, Bertrand; Do, Pascal; Dansin, Eric; Mazieres, Julien; Chouaid, Christos; Perol, Maurice; Barlesi, Fabrice; Robinet, Gilles; Friard, Sylvie; et al.
Here we report our experience of ceritinib in crizotinib-pretreated patients with anaplastic lymphoma kinase ( ALK ) positive ( ALK + ) non-small cell lung cancer (NSCLC) in a French temporary authorisation for use (TAU) study. The French TAU study included crizotinib-pretreated patients with advanced ALK + or ROS proto-oncogene 1 positive ( ROS1 + ) tumours. Patients received oral ceritinib (750 mg·day −1 as a starting dose) and best tumour response (as evaluated by the investigator) and safety were reported every 3 months. A total of 242 TAUs were granted from March 12, 2013 to August 05, 2015. Of the 242 patients, 228 had ALK + NSCLC and 13 had ROS1 + NSCLC. The median age of ALK + patients (n=214) was 58.5 years, 51.9% were female, 70.8% had an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 0–1 and 50.0% had brain metastases. Of the 149 efficacy evaluable ALK + NSCLC patients, 5.4% had a complete response (CR), 47.0% had a partial response (PR) and 22.8% had stable disease (SD). At September 05, 2015, the median duration of ceritinib treatment (n=182) was 3.9 months but 5.5 months for patients (n=71) with a follow-up of ≥12 months. Higher objective response rate (ORR) was observed for patients with ECOG PS 0 to 1 (55.0% versus 42.4%) and those receiving prior crizotinib for >5 months (51.6% versus 36.1%). Treatment-related adverse events (AEs) were reported in 118 of 208 patients (56.7%), the most common being diarrhoea (22.1%) and hepatic toxicity (19.7%). Ceritinib (750 mg·day −1 ) demonstrated efficacy similar efficacy to ASCEND-1, ASCEND-2 and phase 3 ASCEND-5 trials with manageable safety in crizotinib-pretreated patients with ALK + NSCLC. Ceritinib (750 mg per day) showed similar efficacy as in clinical trials in crizotinib-pretreated ALK + NSCLC patients http://ow.ly/8oXe30h27D0